Respostas fisiológicas de homens saudáveis a variações de nível de dificuldade de um videogame tipo Puzzle - Loureiro, Juliana Pereira (2018)
The present study evaluated the physiological responses of cardiorespiratory and electrodermal activity (EDA) of 30 healthy individuals to the difficulty variation of a videogame from electrocardiogram (ECG), respiratory flow and electrodermal response (EDR) signal records. Each participant played three levels of difficulty of the GEMGEM game interspersed by rest. Respiratory indices - respiratory period (RP) and its coefficient of variation (CVRP), heart rate variability indices (HRV) - RMSSD, SDNN and pNN50, as well as Respiratory Sinus Arrhythmia (RSA) were calculated. During the game, HRV, RSA, RP indices decreased, and heart rate (HR) increased. EDR varied among the volunteers, with highest values during the rest stages for some of them. No single index was significantly different between all difficulty levels; a combination of respiratory and electrodermal variables may be able to fully discriminate levels. Future analyses should consider characteristics such as expectation and motivation, as well as the ability of the volunteer in the game.